2012
DOI: 10.1016/j.joca.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Genomic chondrocyte culture profiling by array-CGH, interphase-FISH and RT-PCR

Abstract: While cells of male origin may suffer from an age-related loss of the Y-chromosome, there was no indication of a functional impairment. The data suggest some caution toward applying proliferative steps when considering chondrocytes from elderly male patients for tissue engineering approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In contrast, we observed a significantly lower IL-1b gene expression level after 3D cultivation as compared to monolayer cultivation (P < 0.05). Such increased IL-1b gene expression levels upon monolayer cultivation are uncommon and probably an effect of the diseased cartilage tissue harvested 27,28 . Eger et al reported higher IL-1b levels in osteoarthritic cartilage most likely being an expression of inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we observed a significantly lower IL-1b gene expression level after 3D cultivation as compared to monolayer cultivation (P < 0.05). Such increased IL-1b gene expression levels upon monolayer cultivation are uncommon and probably an effect of the diseased cartilage tissue harvested 27,28 . Eger et al reported higher IL-1b levels in osteoarthritic cartilage most likely being an expression of inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is vital that the risk of tumorigenic transformation due to growth factors’ use in vitro be examined. With increasing reports on the incidence of cytogenetic aberrations during cell ex vivo manipulation 28 , only a few attempts were made to investigate genetic alterations and tumorigenicity in chondrocytes induced by growth factors 29 . Therefore, in the current study, we investigated the biosafety of in vitro expanded human nasal septal chondrocytes (hNSCs) in growth factor cocktail supplemented culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of chromosomal aberrations in the healthy age-matched controls suggest that there is an association between chromosomal aberrations and osteoarthritis (Castellanos et al, 2004). According to Stumm et al (2012), the observed presence or absence of the Y chromosome does not appear to influence the transcriptional activity of chondrocytes.…”
Section: Gonosomal Chromosomesmentioning
confidence: 98%
“…PDLs. Finally, Stumm et al (2012), using human chondrocytes (articular cartilage tissue from patients with total knee replacement surgery and healthy cartilage from human organ donors) reveal autosomal stability, but losses of Y chromosomes.…”
Section: Autosomal Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation